2021
DOI: 10.1177/10780874211016941
|View full text |Cite
|
Sign up to set email alerts
|

Resurgent Ethnicity and Residential Choice Among Second-generation Asian Americans in a Los Angeles Panethnic Suburb

Abstract: We draw on forty-six in-depth interviews with residents of Cerritos, California, a middle-class majority Asian suburb in Los Angeles County to explore the meaning of resurgent ethnicity and the ways in which a racialized identity informs residential preferences and choice among second-generation Asian Americans. Findings suggest that second-generation Asian Americans are choosing to reside in a place that offers cultural and class-based amenities that reflects a multiethnic sensibility. They also make resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This association may exhibit as linear or curvilinear relationships with individuals’ immigration history. The previous research has suggested that first-generation immigrants have higher adherence to their heritage culture compared to their later generations (Salant & Lauderdale, 2003; Ward, 2000), but recent studies have shown that cultural adherence can be strengthened out of a fear of losing cultural roots, leading to intentional adherence to traditional cultural norms for the purpose of maintaining cultural identity (Bhugra & Becker, 2005; Dizon et al, 2021; Patraporn & Kim, 2022).…”
Section: Future Researchmentioning
confidence: 99%
“…This association may exhibit as linear or curvilinear relationships with individuals’ immigration history. The previous research has suggested that first-generation immigrants have higher adherence to their heritage culture compared to their later generations (Salant & Lauderdale, 2003; Ward, 2000), but recent studies have shown that cultural adherence can be strengthened out of a fear of losing cultural roots, leading to intentional adherence to traditional cultural norms for the purpose of maintaining cultural identity (Bhugra & Becker, 2005; Dizon et al, 2021; Patraporn & Kim, 2022).…”
Section: Future Researchmentioning
confidence: 99%